Pembuatan Sirup Glukosa dari Biji Durian dengan Metode Hidrolisis Asam - Fillah, Muhammad Ikhwan; Fauzan, Reza; Harunsyah, Harunsyah (Politeknik Negeri Lhokseumawe, 2024)
The utilization of durian fruit that is consumed is the flesh part with a percentage of only 20-35%. Generally, seeds become waste that is only a small part utilized. Every 100 g of durian seeds contain 51.1 g of water, 46.2 g of carbohydrates, 2.5 g of protein and 0.2 g of fat. This carbohydrate content is higher than cassava 34.7% or sweet potatoes 27.9%. This high carbohydrate content allows durian seeds to be used as a substitute for glucose syrup. Therefore, research must be conducted by utilizing durian seed waste to make glucose syrup. The purpose of this study was to determine the effect of time and temperature on reducing sugar levels. The method for this study used the acid hydrolysis method and the search for reducing sugar levels used the lufft-schoorl method. This study used time variations of 60, 90, 120, 150, 180 minutes and temperature variations of 90, 95, 100, 105, 110°C in the acid hydrolysis method which used 3% HCl solvent. From the results of the study, it was found that hydrolysis time and hydrolysis temperature greatly influenced reducing sugar. The higher the time and temperature, the higher the reducing sugar content obtained. The highest reducing sugar content was obtained at 19.55% and the lowest water content was 16.30% which was obtained at a temperature of 110oC and a time of 180 minutes.